2019
DOI: 10.1159/000496341
|View full text |Cite
|
Sign up to set email alerts
|

Complex Neurological Phenotype in Female Carriers of <b><i>NHE6</i></b> Mutations

Abstract: Mutations in NHE6 (also termed SLC9A6) cause the X-linked neurological disorder Christianson syndrome (CS) in males. The purpose of this study was to examine the phenotypic spectrum of female carriers of NHE6 mutations. Twenty female carriers from 9 pedigrees were enrolled, ranging from approximately age 2 to 65. A subset of female carriers was assessed using standardized neuropsychological measures. Also, the association of NHE6 expression with markers of brain age was evaluated using 740 participants in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“… 2 Moreover, it was found in postmortem brain tissues that decreased NHE6 expression was correlated with greater tau deposition. 10 Our study further suggests that SLC9A6 variations might be associated with tau-related syndromes in females in late life.…”
Section: Discussionsupporting
confidence: 64%
“… 2 Moreover, it was found in postmortem brain tissues that decreased NHE6 expression was correlated with greater tau deposition. 10 Our study further suggests that SLC9A6 variations might be associated with tau-related syndromes in females in late life.…”
Section: Discussionsupporting
confidence: 64%
“…Moreover, deposition of tau may be mediated by the interaction with the mutant SLC9A6 protein (Garbern et al, 2010). After using a conservative genome-wide correction, it was found that the low expression of SLC9A6 was significantly related to increased tau deposition (Pescosolido et al, 2019). The most obvious pathological event in several neurodegenerative diseases is the aggregation of tau subtypes into the filamentous content of neurons, resulting in hyperphosphorylation of tau proteins (Buée et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Contrast to male, female variant carriers show milder phenotypes with variable penetrance 4,10 . Affected CS patients show a remarkable neurological symptom may be due to high‐level expression of mutant SLC9A6 gene in the central nervous system 11,12 …”
Section: Introductionmentioning
confidence: 99%
“… 4 , 10 Affected CS patients show a remarkable neurological symptom may be due to high‐level expression of mutant SLC9A6 gene in the central nervous system. 11 , 12 …”
Section: Introductionmentioning
confidence: 99%